Syncopation as structure bootstrapping: the role of asymmetry in rhythm and language - Fiorin, Gaetano; Delfitto, Denis (Frontiers in Psychology, 2024)
Syncopation – the occurrence of a musical event on a metrically weak position preceding a rest on a metrically strong position – represents an important challenge in the study of the mapping between rhythm and meter. In this contribution, we present the hypothesis that syncopation is an effective strategy to elicit the bootstrapping of a multi-layered, hierarchically organized metric structure from a linear rhythmic surface. The hypothesis is inspired by a parallel with the problem of linearization in natural language syntax, which is the problem of how hierarchically organized phrase-structure markers are mapped onto linear sequences of words. The hypothesis has important consequences for the role of meter in music perception and cognition and, more particularly, for its role in the relationship between rhythm and bodily entrainment.